Comparable survival in rats with intracranial glioblastoma irradiated with single-fraction conventional radiotherapy or FLASH radiotherapy - Liljedahl, Emma; Konradsson, Elise; Linderfalk, Karin; Gustafsson, Emma; Petersson, Kristoffer; Ceberg, Crister; Redebrandt, Henrietta Nittby (Frontiers in Oncology, 2024)
Background: Radiotherapy increases survival in patients with glioblastoma.However, the prescribed dose is limited by unwanted side effects on normal tissue.Previous experimental studies have shown that FLASH radiotherapy (FLASH-RT) can reduce these side effects. Still, it is important to establish an equal anti-tumor efficacy comparing FLASH-RT to conventional radiotherapy (CONV-RT).: Fully immunocompetent Fischer 344 rats with the GFP-positive NS1 intracranial glioblastoma model were irradiated with CONV-RT or FLASH-RT in one fraction of 20 Gy, 25 Gy or 30 Gy. Animals were monitored for survival and acute dermal side effects. The brains were harvested upon euthanasia and tumors were examined post mortem. Results: Survival was significantly increased in animals irradiated with CONV-RT and FLASH-RT at 20 Gy and 25 Gy compared to control animals. The longest survival was reached in animals irradiated with FLASH-RT and CONV-RT at 25 Gy.Irradiation at 30 Gy did not lead to increased survival, despite smaller tumors. Tumor size correlated inversely with irradiation dose, both in animals treated with CONV-RT and FLASH-RT. Acute dermal side effects were mild, but only a small proportion of the animals were alive for evaluation of those side effects.The dose response was similar for CONV-RT and FLASH-RT in the present model. Tumor size upon the time of euthanasia correlated inversely with the irradiation dose.